Application of small-angle scattering to study the effects of moisture content on a native soy protein - Kealley, Cat; Elcombe, M.; Wuhrer, R.; Gilbert, E. (2008)
The nano- and microstructure of glycinin, a soybean protein, has been investigated as a function of moisture for moisture contents between 4 and 21 wt%. Glycinin exhibits peaks in the small-angle region whose positions show minimal change with X-rays for samples up to 13% moisture. However, the use of neutron scattering, and the associated enhancement in contrast, results in the Bragg peaks being well resolved up to higher moisture contents; the associated shift in peak positions between 4 and 21% moisture are consistent with the expansion of a hexagonal unit cell as a function of moisture content. A Porod slope of ~-4 indicates that the interface between the 'dry' protein powder and the surrounding medium at a length-scale of at least 3 µm down to ~20 nm is smooth and sharp. Scanning electron microscopy indicates that the powders, with low moisture content, have a porous appearance, with the porosity decreasing and microstructure expanding as the moisture content increases. © 2008 International Union of Crystallography.